Pengaruh Kewirausahaan Sosial dan Kolaborasi Komunitas Terhadap Produktivitas Ekonomi Wanita Buddhis - Sriyana Sriyana; Partono Nyanasuryanadi; Tjhia Khie Kiong (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study investigates the impact of social entrepreneurship and community collaboration on the economic productivity of Buddhist women, specifically within the Indonesian Buddhist Women (WBI) community in Jambi City. A quantitative associative method was applied, collecting data from 41 respondents using Likert-scale questionnaires, which were analyzed through multiple linear regression. The results reveal that social entrepreneurship significantly enhances economic productivity (β = 0.698, *p* < 0.001). In contrast, community collaboration does not show a significant partial effect (β = 0.136, *p* = 0.265). However, both variables simultaneously account for 79.2% of the variance in economic productivity (F = 72.341, *p* < 0.001). These findings highlight the strategic role of social entrepreneurship rooted in Buddhist ethics such as sammā ājīva (right livelihood) in economic empowerment. The study recommends strengthening participatory collaboration frameworks and integrating Buddhist values into entrepreneurial training programs.